On Measuring miRNAs after Transient Transfection of Mimics or Antisense Inhibitors - Thomson, Daniel W. (Public Library of Science, 2013)
The ability to alter microRNA (miRNA) abundance is crucial for studying miRNA function. To achieve this there is widespread use of both exogenous double-stranded miRNA mimics for transient over-expression, and single stranded antisense RNAs (antimiRs) for miRNA inhibition. The success of these manipulations is often assessed using qPCR, but this does not accurately report the level of functional miRNA. Here, we draw attention to this discrepancy, which is overlooked in many published reports. We measured the functionality of exogenous miRNA by comparing the total level of transfected miRNA in whole cell extracts to the level of miRNA bound to Argonaute following transfection and show that the supraphysiological levels of transfected miRNA frequently seen using qPCR do not represent the functional levels, because the majority of transfected RNA that is detected is vesicular and not accessible for loading into Argonaute as functionally active miRNAs. In the case of microRNA inhibition by transient transfection with antisense inhibitors, there is also the potential for discrepancy, because following cell lysis the abundant inhibitor levels from cellular vesicles can directly interfere with the PCR reaction used to measure miRNA level.